Pengelolaan Perpustakaan Sekolah Di Sekolah Menengah Pertama (SMP) Islam Polehan – Malang - Risa Kharisma (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
This research or research focuses on describing the management of educational libraries in Islamic Junior High School Polehan – Malang. This description of the library is reviewed from several sources by explaining each discussion from the beginning of the library implementation planning process to the library evaluation process. The research method in this study is a case study, by conducting field research and collecting data from observations, documentation or interviews. The results of this study indicate that there are activities in the management of library administration and management of library library materials. Both types of library management must begin with a clear formation of the library organizational structure which will facilitate the overall library management process. The clarity of the organizational structure of the library can be seen from the existence of the Head of the Library and Library Staff.Management of library administration such as the vision and mission, the organizational structure, the rules, library facilities, and library services. The library management of the Islamic Middle School of Polehan – Malang has been trying to be maximized as much as possible even though there are many limitations. While the management of library library materials such as procurement of books, flow management of library materials, collection of library materials, and storage of library materials. The management of library materials at the Islamic Middle School in Polehan – Malang during the pandemic was very different, where before the pandemic library services were carried out directly by library staff and students, then during the pandemic the guardians were allowed to come to school to borrow library books.